Effect of Ag concentration on the thermal behavior of the Cu-10 mass% Al and Cu-11 mass% Al alloys - Magdalena, A. G. [UNESP]; Adorno, A. T. [UNESP]; Silva, R. A. G. [UNESP]; Carvalho, T. M. [UNESP] (Springer, 2009)
In this work the effect of Ag concentration on the thermal behavior of the Cu-10 mass% Al and Cu-11 mass% Al alloys with additions of 4, 6, 8 and 10 mass% Ag was studied using differential scanning calorimetry (DSC), in situ X-ray diffractometry (XRD) and scanning electron microscopy (SEM). The results showed that for the Cu-10 mass% Al alloy Ag addition induce the beta'(1) phase formation and for the Cu-11 mass% Al alloy these additions increase the amount of martensite formed on quenching and decrease the stability range of this phase on heating.
Keywords: Ag addition; Al addition; thermal behavior